Health impact assessment of an urban regeneration project: opportunities and challenges in the context of a southern European city. Issue 11 (24th November 2009) - Bacigalupe, A; Esnaola, S; Calderón, C; Zuazagoitia, J; Aldasoro, E
Abstract : Background: Social values and the political context have an influence on the use and spread of health impact assessment (HIA). In Spain, there is little experience in HIA but some regional governments are already introducing it. The aim of this article is to describe the health impacts of a local regeneration project to improve accessibility in a neighbourhood of Bilbao (Spain), and discuss the main difficulties, opportunities and challenges of the process, considering the specificities of the social and political context. Methods: A concurrent and prospective assessment, based on a broad model of health, was carried out following the Merseyside guidelines. A literature review, community profiling and qualitative data collection were undertaken. Profound involvement of members of the community and key informants was judged as essential in the HIA process. Results: The overall expected effect of the new lifts, roads, park and the rainwater collection system was positive. Uncertain or negative impacts were identified in some of those areas, and also concerning the burying of four high-voltage power lines. Historical and current characteristics of the community were highly influential on the way local people perceived the project and its impacts. Likewise, the way in which processes of planning and implementation were developing also played an important role. Conclusion: The spread of HIA in southern European countries will depend on the progressive introduction of values underlying HIA, as well as on the promotion of intersectoral work, a better knowledge of the social model of health and community's participation in policy making.